PREDICTION OF GENITAL ENDOMETRIOSIS IN UKRAINIAN GIRLS DEPENDING ON THE FEATURES OF SONOGRAPHIC INDICATORS OF THE UTERUS AND OVARY - Nyzova, O.A.; Chaika, H.V.; Ishchuk, O.H.; Kucherenko, O.S.; Gunas, I.V. (World of Medicine and Biology, 2025)
In Ukrainian girls without and with somatotype, based on the features of the sonographic dimensions of the uterus and ovaries, reliable discriminant models were constructed that allow predicting the possibility of genital endometriosis with high probability (without taking into account somatotype – the correctness of the classification matrix is 98.8% of cases, Wilks' Lambda statistics=0.142, p
Keywords: obstetrics and gynecology; genital endometriosis; Ukrainian girls; sonography; uterus; ovaries; menstrual cycle; somatotype; discriminant analysis